First-principles study on segregation anisotropy of grain boundaries in Pt–Au alloys - Yao, Xin; Guo, Ya-Fang; Li, Wei; Kokko, Kalevi; Li, Changle; Vitos, Levente (AIP Publishing, 2025)
Gold (Au) segregation at the Pt grain boundaries (GBs) plays an important role on the properties of Pt-based alloys. It was reported that the close-packed GBs and the open GBs exhibit different segregation behaviors, and the origin of which is still unclear. Based on density functional theory (DFT) as implemented in the exact muffin-tin orbitals method (EMTO) and the full charge density technique, we investigate the impact of bulk composition and temperature on the segregation behaviors of the Sigma 3(111)[1-10] , Sigma 5(310)[001] and Sigma 9(221)[1-10] symmetric tilt GBs in Pt-Au alloys. It is revealed that the segregation driving forces are correlated with the large local volume near the GB and the miscibility gap in Pt-Au alloys. At finite temperatures when the configurational entropy is considered, a competition between the chemical driving force and the configurational entropy is responsible for the segregation anisotropy in Pt-Au alloys. Moreover, the bulk composition has a small effect on the segregation energy, but strongly impacts the equilibrium concentration profiles at finite temperatures.The present study provides a theoretical analysis for the segregation anisotropy, and the methodology ultilized in this work can be generalized to other binary or multi-component dilute or concentrated alloys while the composition variation is involved. (c) 2025 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution-NonCommercial-NoDerivs 4.0 International (CC BY-NC-ND) license (https://creativecommons.org/licenses/by-nc-nd/4.0/).